Simulation and Research of Methane Premixed Combustion Characteristics Based on Constant Volume Combustion Chamber with Different Ignition Modes - Yue Wang; Xin Zhang; Xinmiao Fan; Yanfei Li (Energies, 2023)
Dual spark plug ignition can accelerate the burning velocity of nature gas and improve the engine performance. However, the mechanism between the two flames and the disturbance characteristics of flame to flow field during the combustion process under different ignition strategies are still unclear. In order to reduce the interference of other external factors, this paper is based on the CFD software CONVERGE 3.0, using G equations combined with SAGE detailed chemical reaction mechanism, the combustion model is constructed based on the closed constant volume combustion chamber. The accuracy of the model was verified using experimental data. The methane–air premixed combustion process under different ignition strategies (single spark ignition, dual spark synchronous ignition and dual spark asynchronous ignition) was simulated using this model. The results show that the flame propagation speeds under the dual spark ignition plan are all smaller than that of single spark ignition due to the inhibition of the opposite side flame. However, it still has obvious fast combustion characteristics, shortens the combustion duration and improves the heat release rate. The flame stability is optimum under synchronous ignition with the pressure offsetting effect, and with the increase in the ignition interval, the flame stability decreases, and the disturbance of the flow field gradually increases. There is little effect of ignition position on combustion pressure and heat release rate. Compared with single spark ignition and dual spark asynchronous ignition, dual spark synchronous ignition has better combustion characteristics. It can improve thermal efficiency while ensuring flame stability. This is a key technology for improving the natural gas engine performance.